Analysis of Halal Certification Readiness Level and Strategy to Increase Competitiveness of MSMEs in Bangkalan Regency: Porter Diamond Model - Faizal Amir; Fajar, Fajar (Jurnal Ekonomi, 2024)
Bangkalan Regency is one of the districts in Indonesia where 98.86 of its population are Muslims. In addition, Bangkalan is also known as the City of Dhikr and Solawat. This shows that the production and availability of halal products are very urgent to be the main concern due to the strong identity of Islam. This study is expected to be able to measure the level of readiness of MSMEs in Bangkalan Regency to carry out halal certification and prepare strategies to increase competitiveness through a questionnaire that has been prepared, considering the potential of Bangkalan Regency as a Muslim region and has many superior MSMEs that are also export-oriented. The purpose of this study specifically is to analyze the level of readiness of MSMEs in Bangkalan Regency to carry out halal certification and prepare strategies to increase their competitiveness. This study is descriptive quantitative. The research technique is a survey using questionnaires and interviews as data collection tools in addition to literature studies. There are four MSMEs that are the samples of this study, namely Lamora MSMEs, sempeng cracker producers, Terung MSMEs, Budi Jaya MSMEs and Satru MSMEs. Employing a rigorous assessment methodology, this study utilized the Macroergonomic Organizational Questionnaire Survey (MOQS) and instruments derived from the LPPOM MUI Halal Assurance System's eleven criteria and Porter's Diamond Model to evaluate the preparedness of Micro, Small, and Medium Enterprises (MSMEs) for halal certification. The analysis reveals a spectrum of readiness, with Budi Jaya MSMEs, a processed salak producer, demonstrating the highest level of preparedness, while Lamora, Terung, and Satru MSMEs require strategic enhancements in various operational aspects to meet halal certification standards. Crucially, in anticipation of the JPH Law's enforcement, all assessed MSMEs are urged to proactively strengthen their halal branding, necessitating a concerted focus on facility upgrades, the sourcing of certified halal materials, and the refinement of overall product identity.